“Театр у кошику”: українська класика і сучасна естетика - Пігель, Ю. (Студії мистецтвознавчі, 2008)
In the article “Theatre in a basket” the most significant theatre performances are reviewed: “White butterflies, woven chains” – V. Stefanyk, “Stolen happiness” – I. Franko, “On blood field” – Lesya Ukrainka, “I am coming, Christ” – H. Luzhytsky, as well as the most typical author’s approaches to he national authentic reality. The theatre imagery is based on archetypes and symbols, which is revealed by the instrument of stage costume.